Sunday

April 20, 2014

April 20, 2014

Posted by **Anonymous** on Thursday, March 25, 2010 at 3:38am.

y=(3x-1)(x-2)^2

- Math -
**Reiny**, Thursday, March 25, 2010 at 9:15amUse the product rule in combination with the chain rule to find dy/dx

then set that equal to zero to solve for x

sub the x back into the original to find the points.

**Related Questions**

math - f(x)=-x^3+3x^2+9x-5 asked to find the stationary points this was my ...

math - this question concerns the function f(x)=-2x3+3x2+12x+10 (a)find the ...

maths - given the curve y=2x/(1+x^2)^2 (a) prove that dy/dx =2(1-x^2)/(1+x^2)^2...

maths - find the stationary points of the following f(x)=x^3-3x^2-24x-7

maths - find the y coordinates of each stationary points f(0). f(x)=x^3-3x^2-24x...

maths - find the stationary points of the following function f(x)=x^3-3x^2-24x-7

Math - Given [(x-5)/(x-3)]^2 . Find any stationary points and any points of ...

calculus - consider the function; f(x)=x^4-3x^2-1 a) Find all the point where f...

calc - Given [(x-5)/(x-3)]^2 . Find any stationary points and any points of ...

Maths - 9. consider the function y=e^-x sin x where pie < x < pie find dy/...